Diode Rectifier Unit Based LFAC Transmission for Offshore Wind Farm Integration - Yingjie TANG; Zheren ZHANG; Zheng XU (Zhongguo dianli, 2020)
The offshore wind power, which is high in density and small in fluctuation, will be the focus for wind power development in the future. Up to now, the offshore wind power transmission projects in operation have mostly adopted VSC-HVDC technology, whereas their capital cost is relatively high. So, this paper proposes a diode uncontrolled unit (DRU) based low frequency alternative current (LFAC) transmission scheme for the offshore wind farms, in which the offshore platform of the rectifier is cancelled and the rectifier in the traditional AC-DC-AC frequency converter is substituted by the DRU, thus significantly reducing the project investment and operating cost. Since the DRU is uncontrolled, a corresponding control strategy of the offshore wind turbines is proposed for LFAC transmission system, in which the machine side converter (MSC) controls the DC voltage and the grid side converter (GSC) implements the maximum power point tracking (MPPT) and AC voltage control together in the global unified reference coordinate system. Case simulations in PSCAD/EMTDC were carried out in the end to study the system response to typical operating conditions including wind power fluctuation and three-phase faults in the onshore grid and offshore grid, and the feasibility of the proposed scheme is verified.